Revolutionizing Organizational Efficiency with Digital Transformational Leadership: The Bridging Role of Employee Performance and Engagement - Mariana (Universitas Pelita Harapan, 2025)
This study investigates the influence of digital transformational leadership on organizational efficiency, focusing on the mediating effects of employee performance and work engagement. In an increasingly digitalized business environment, leaders must leverage technology to guide their teams toward enhanced productivity, innovation, and agility. However, only some studies have comprehensively examined the intersection of digital leadership behaviors, employee- related factors, and efficiency metrics. Adopting an exploratory approach, this paper synthesizes recent literature (2018–2023) from Scopus-indexed journals to identify patterns and gaps in the current understanding of how digital transformational leadership can foster a high-performing, engaged workforce that drives improved organizational efficiency. The review involved searching key terms such as